A survey of Israel's history - Wood, Leon James, 1918-77; O'Brien, David 1940- (Grand Rapids, MI Zondervan, 1986)
Includes bibliographical references, indexes, maps, charts, diagrams.
Keywords: Bible. O.T. -- history of Biblical events; Jews -- history -- to AD 70.